Nilai Pendidikan Tauhid dalam Film â€œMunafik 2â€ Karya Syamsul Yusof - Aminah, Dewi; Pasya, Rayi; Rahmawangsih, Yuli Altri (Bestari | Jurnal Studi Pendidikan Islam, 2020)
This study aims to elaborate the values ​​of Islamic education in the film "Munafik 2" by Syamsul Yusof. This type of research is qualitative research, namely research on descriptive research and tends to use analysis. The data collection techniques used are documentation techniques and library research (library research). The collected data were analyzed and classified with the educational value of Tauhid in the film "Munafik 2" by Syamsul Yusof. By focusing on the discussion on monotheism education material in the film. The results showed that the value of tauhid education in this film includes Tauhid Rububiyah, which is to believe that Allah is the only ruler of the universe. Rububiyah monotheism related to the pillars of faith, namely faith in Allah, angels, the apostles, the books of Allah, qadha ', and qadar. This film also contains the values ​​of tauhid uluhiyah / ubudiyah, namely the obedience of a servant in the eyes of Allah SWT, such as prayer, ta'awun, da'wah. While the work was intended only to get closer and worship Allah SWT. Finally, this film also contains the value of tauhid asma 'wa shifat, namely those with good names and noble traits that show absolute perfection. In this context it can be taken the form of implementation from imitating Allah's attributes. Like piety, the form of imitating the nature of Allah al-Akhir, which is the ultimate substance, tawakal, is the form of the nature of Allah al-Vice, which is the Most Preserver or the Most Reliable.